R5S4TRAIL ameliorates radiation-induced pulmonary fibrosis by alleviating inflammatory responses and promoting apoptosis of fibroblasts - Zhao, Yaqin; Wei, Yuanfeng; Hou, Wanting; Huang, Xianzhou; Li, Qiaoqi; Yi, Cheng (Frontiers in Immunology, 2025)
BackgroundRadiation-induced pulmonary fibrosis (RIPF) is a chronic, fatal and irreversible disease that develops after a consequence of thoracic radiation therapy and few effective treatments have been developed for this condition. Repeated inflammation and excessive accumulation of fibroblasts are features of RIPF. Thus, reducing inflammation and inducing lung fibroblast apoptosis may be an effective strategy for RIPF. Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL), as a natural immunomodulator, can specifically bind to death receptors (DRs) and selectively induce apoptosis in many cells. In our research, we have constructed a novel TRAIL mutant with CPP-like and Smac-like structure (R5S4TRAIL) and aim to explore the role and molecular mechanism of R5S4TRAIL in RIPF.MethodsFirstly, the RIPF model was established in C57BL/6 mice. Then, the mice were treated with saline (Con group), dexamethasone (Dex group), or R5S4TRAIL (RST group). The remission of RIPF was evaluated by micro-CT, Masson and hematoxylin-eosin (HE) staining. Next, the molecular mechanisms of R5S4TRAIL in RIPF were explored in vivo and vitro.ResultsWe successfully established the RIPF model and found that R5S4TRAIL treatment could regulate the expression of inflammatory-related cytokines and attenuate the inflammatory response. Meanwhile, R5S4TRAIL treatment could upregulate DR5 expression and induce apoptosis in lung fibroblasts. Briefly, treatment with R5S4TRAIL could alleviate RIPF.ConclusionsR5S4TRAIL has the potential to ameliorate RIPF by alleviating inflammatory responses and promoting apoptosis of fibroblasts.